1852 Terr. of N.M. Laws 66-69, An Act Prohibiting the Carrying a Certain Class of Arms, within the Settlements and in Balls, § 1 - (:unkn) unknown (General Publisher, 1853)
That each and every person is prohibited from carrying short arms, such as pistols, daggers, knives, and other deadly weapons, about their persons concealed, within the settlements, and any person who violates the provisions of this act, shall be fined in a sum not exceeding ten dollars, nor less than two dollars, or shall be imprisoned for a term not exceeding fifteen days nor less than five days.
--
Keywords: CARRY - CONCEALED